Ecoliteracy Profile of Grade 1 Elementary School Students: Profil Ekoliterasi Siswa Kelas 1 Sekolah Dasar - Diana Mustafida; Fitria Eka Wulandari (Academia Open, 2021)
This study aims to reveal the ecoliteracy profile of the students of SD Negeri 2 Sedatigede. The research method used is a quantitative survey. The population used was all first grade students of SD Negeri 2 Sedati and the samples taken in this study were 92 students. The collection of samples using a sampling technique is a quota sampling technique. Data collection techniques using test techniques. The research instrument used in the form of a test about the ability of ecoliteracy. The test results were then analyzed using a formula and the ecoliteracy ability was described into 4 criteria, namely very positive, positive, negative, and very negative. Based on the results of the analysis, it was concluded that students at SD Negeri 2 Sedatigede had ecoliteracy skills at a very positive level with an average of 56% as many as 52 students, at a positive level with an average of 32% as many as 29 students, at a negative level with an average of 12% as many as 16 students, and the level is very negative with an average of 0% as many as 0 students from the total number of students in class I Keywords –Ecoliteracy, Modification, Profile